Multipath interference canceller for high-speed packet transmission with adaptive modulation and coding scheme in W-CDMA forward link - Higuchi, K.; Fujiwara, A.; Sawahashi, M. (IEEE journal on selected areas in communications, 2002)
This paper proposes a multipath interference canceller (MPIC) associated with orthogonal code-multiplexing that achieves much higher peak throughput than 2 Mbit/s with adaptive data modulation for high-speed packet transmission in the wideband direct sequence-code division multiple access (W-CDMA) forward link, and evaluates its throughput performance by computer simulation. The simulation results elucidate that sufficient multipath interference (MPI) suppression is achieved by a four-stage MPIC with 6-12 orthogonal code-multiplexing using one iterative channel estimation with pilot and decision feedback data symbols and further that the interference rejection weight control according to the number of observed multipaths is effective in improving the throughput. It is also demonstrated that MPIC exhibits a superior MPI suppression effect to a chip equalizer in the lower received signal energy per bit-to-background noise spectrum density (E/sub b//N/sub 0/) channel around 0-3 dB owing to the successive channel estimation at each stage. We show that the maximum peak throughput using MPIC is approximately 2.1 fold that without MPIC in a two-path and three-path Rayleigh fading channel and that the peak throughput of 8.0 Mbit/s is achieved using 64 QAM data modulation in a two-path fading channel within a 5 MHz bandwidth. Furthermore, the required average E/sub b//N/sub 0/ for satisfying the same throughput with MPIC is decreased by more than 2.0 dB.